Choosing Wisely: The Canadian Society of Nephrology's List of 5 Items Physicians and Patients Should Question. Issue 1 (28th February 2017) - Chan, Emilie; Hemmelgarn, Brenda; Klarenbach, Scott; Manns, Braden; Mustafa, Reem; Nesrallah, Gihad; McQuillan, Rory
Purpose of review: The purpose of this review is to contribute to the Choosing Wisely Canada campaign and develop a list of 5 items for nephrology health care professionals and patients to re-evaluate based on evidence that they are overused or misused. Sources of information: A working group was formed from the Canadian Society of Nephrology (CSN) Clinical Practice Guidelines Committee. This working group sequentially used a multistage Delphi method, a survey of CSN members, a modified Delphi process, and a comprehensive literature review to determine 10 candidate items representing potentially ineffective care in nephrology. An in-person vote by CSN members at their Annual General Meeting was used to rank each item based on their relevance to and potential impact on patients with kidney disease to derive the final 5 items on the list. Key messages: One hundred thirty-four of 609 (22%) CSN members responded to the survey, from which the CSN working group identified 10 candidate-misused items. Sixty-five CSN members voted on the ranking of these items. The top 5 recommendations selected for the final list were (1) do not initiate erythropoiesis-stimulating agents in patients with chronic kidney disease (CKD) with hemoglobin levels greater than or equal to 100 g/L without symptoms of anemia; (2) do not prescribe nonsteroidal anti-inflammatory drugs for individuals with hypertension or heart failure or CKD of all causes, including diabetes; (3) do not prescribe angiotensin-converting-enzyme inhibitors in combination with angiotensin II receptor blockers for the treatment of hypertension, diabetic nephropathy or heart failure; (4) do not initiate chronic dialysis without ensuring a shared decision-making process between patients, their families, and their nephrology health care team; and (5) do not initiate dialysis in outpatients with CKD category G5-ND in the absence of clinical indications. Limitations: A low survey response rate of both community and academic nephrologists could contribute to sampling bias. However, the purpose of this report is to generate discussion, rather than study practice variation. Implications: These 5 evidence-based recommendations aim to improve outcomes and individualize care for patients with kidney disease, while reducing inefficiencies and preventing harm.